Diversity of Durian (Durio zibethinus Murr) in Aik Bual Village, Central Lombok Regency - Evy Aryanti; Kurniasih Sukenti; Nur Indah Julisaniah; Aida Muspiah; Sukiman Sukiman; Deandra Alma Thalita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Aik Bual Village has a durian community that grows durian, both local and introduced durian. The purpose of this study was to obtain information on the diversity and level of similarity of durian accessions in Aik Bual village, Central Lombok Regency in an effort to save and develop durian germplasm (Durio zibethinus) to obtain the diversity and level of similarity of durian accessions (D. zibethinus) in Aik Bual village, Central Lombok Regency. The study was conducted from December 2023 to October 2024. Sampling of D. zibenthinus accessions was collected using the exploration method. Morphological characterization data was analyzed using NTSys pc. 2.02i software. Durio kutejensis known as Lai was used as an outgroup in this study. The results of the study found eight accessions of D. zibethinus, consisting of introduced durian accessions such as Musang King, Black Thorn (Ochee), Montong, Kane, and Otong, while local durian accessions such as Mentega, Susu, and Sukun. Kinship analysis with NTsys resulted in two main groups, the first group consisting of Montong, Kane and Otong while the second group consisted of Musang King, Ochee, Sukun, Mentega and Susu.